Nutrition Levels of Liquid Organic Fertilizer from Onion Skin (Allium cepa. L) with EM-4 Bioactivator - Gustria Ernis; Donna Sagita Mala; Amelisa Okta; Doni Notriawan; Muhammad Adeng Fadila (Universitas Nusa Bangsa, 2023)
The high production of shallots (Allium cepa. L) causes a large amount of shallot waste in the form of shallot skins, which are organic wastes with a light weight, easily dispersed, disturbing the landscape and polluting the environment as well as being a source of disease. So that it is necessary to process waste into materials that have useful and even economic value, one of which is Liquid Organic Fertilizer (POC). The purpose of this study was to determine the levels of macro and micro nutrients in POC with varying concentrations of EM-4 bioactivator. In this study, the manufacture of POC with various concentrations of bioactivator 0, 25, 50, and 100 mL with a fermentation time of 14 days. Then carried out physicochemical observations, namely observing physical and chemical changes ranging from viscosity, color, odor and the presence or absence of gas in the POC made. The resulting POC was then tested for macro-nutrients (N, P, K and C-organic) and micro-nutrients (Fe, Mn, and Cu) using AAS and UV-Vis spectrophotometer. In this study, the best POC of onion peel waste was obtained at a concentration of 100 mL bioactivator with macronutrients N, P, K, C-Organic, each of which was 0.71; 1.45; 0.36 and 4.7%; while the content of micronutrients Fe, Mn, and Cu were 0.037, respectively; 0.0052, and 0.198%. It can be concluded that the levels of macro and micro nutrients have complied with SNI 19-7030-2004 except for C-organic elements which are still far below the standard, and POC made from onion skin has a high phosphorus content, so it is very suitable for use in plants that have high levels of phosphorus. require growth regulators (ZPT), especially for root growth.